Clinical, nutritional, anthropometric indicators and frequency of occurrence of Ala16Val (rs4880) polymorphic locus of the MnSOD gene in vibration disease comorbid with arterial hypertension - Gorbunova, A. M.; Gerasimenko, O. N.; Shpagin, I. S.; Medvedkina, M. S.; Maksimov, V. N.; Nikolaev, Yu. A. (Sibirskiĭ nauchnyĭ medit︠s︡inskiĭ zhurnal, 2024)
The continuing interest in the problem of vibration disease (VD), especially when combined with arterial hypertension (AH), is due to the steady development of industrial sectors associated with vibration acceleration and the tendency towards the early development of AH. Aim of the study was to investigate the features of clinical, nutritional and anthropometric indicators and frequency of occurrence of Ala16Val (rs4880) polymorphic locus of the manganese superoxide dismutase ( MnSOD ) gene in VD combined with AH. Material and methods . 431 people were examined, among them 104 patients with VD stage I, 101 – with VD stage I in combination with AH I–II stage, 107 – with AH I–II stage, without contact with vibration, and 119 people working at the same enterprise without contact with vibration, without signs of hypertension. A complex of clinical, anthropometric, laboratory, functional and genetic studies has been carried out. Results . In case of VD comorbid with AH, the frequency of complaints, both general and specific, significantly increases compared to other groups. Body mass index, waist circumference / hip circumference (WC/HC) ratio, fat mass increase, extracellular fluid content with a decrease in active cell mass, musculoskeletal mass and phase angle compared with the control group. An imbalance of nutrition in terms of macro- and micronutrients, an increased content of the fat component in the diet with a deficiency in the diet of omega-3 polyunsaturated fatty acids has been established. In persons with VD and AH, the C/C genotype, which is more common in healthy people, is registered in only 16% of cases, while the polymorphic variant T/T is in 29 %, which exceeds the corresponding value in the control and isolated AH groups by 1.9 and 1.5 times, respectively. Discussion . The common pathogenetic features of VD and AH lead to the development of adipose tissue dysfunction and trophological insufficiency. There is no doubt that hypertension is associated with increased body weight, obesity, and adipocytokine serum concentration. An indicator of a high risk of developing cardiovascular pathology, including heart attack, stroke, is an increase in the WC/HC index. The role of the Ala16Val polymorphism of the MnSOD gene in the formation of AH and some variants of occupational diseases has been shown in a number of studies. Conclusions . The variant of VD, comorbid with AH, is characterized by a significant increase in the frequency of detection of the T/T genotype in the polymorphic locus Ala16Val (rs4880) of the MnSOD gene in combination with an altered nutritional and anthropometric status of such patients. The presence of this polymorphism may be associated with an increased risk of developing concomitant vascular pathologies in VD, however, in combination with malnutrition and associated changes in anthropometric parameters, this risk increases many times over. Thus, early diagnosis of the risk of developing comorbid vascular pathology in VD can be aimed at identifying the genotype, and prevention can be aimed at modifying nutrition.